Morphology and structural Characteristics of TiO2-SiO2 binary glass deposition particles. Issue 1 (January 2021) - Zhang, Chenyang; Nie, Lanjian; Xiang, ZaiKui; Rao, Chuandong; Fu, Bo; Wang, Lei; Shao, Zhufeng; Wang, Hongjie; Jia, Yanan; Wang, Hui; Wang, Yufen
Abstract: TiO2 -SiO2 is a kind of binary component glass material with excellent properties such as high heat impact resistance, welding ability, and the size of the material is insensitive to temperature change. Based on the principle of Chemical Vapor Deposition (CVD), we used silicon tetrachloride and titanium tetrachloride as the raw materials for the preparation of this glass. In this research, we studied the morphology, structure, and particle size distribution of TiO2 -SiO2 binary glass particles. The experimental results show that the deposition particles are spherical amorphous nanoparticles with a size of about 100nm, and there is no SiO2 or TiO2 crystalline phase in the particles. This particle structure overcomes the characteristic that TiO2 is easily crystallized in other preparation methods, making preparation for TiO2 -SiO2 binary glass possible.